Effects of pesticides on photosynthesis of marine phytoplankton (Bangladesh Journal of Botany, 2018)
Toxicity of pesticides, namely chlorpyrifos, malathion, cypermethrin, lambda-cyhalothrin and buctril were tested on the photosynthetic behavior of marine phytoplankton. The phytoplankton population was exposed to 0.01, 0.03, 0.06 and 0.09 ppm of test pesticides. The toxicity of pesticides stands in the order of lambda-cyhalothrin > chlorpyrifos > buctril > malathion > cypermethrin. The most toxic pesticide was lambda-cyhalothrin having IC50 value of 0.014 ppm. Toxicity of cypermethrin was less on phytoplankton compared to others.